PEMIKIRAN HASAN AL-BANNA TENTANG PENDIDIKAN ISLAM - Syaflin Halim (Program Pascasarjana UMSB, 2019)
Hasan al-Banna as a reformer in Islam emerged as a pragmatic leader in society, he was not a systematic theorist. Hasan al-Banna developed education for Muslim communities by relying on the pulpit of the mass organization and presented a charismatic leader who inspired thousands of Egyptian Muslim communities and even the Islamic world to carry out its programs with full faith and sincerity. This type of research is in the form of library research. The approach used in this research is descriptive analysis method. Research data collection techniques are the identification of discourse from books, papers or articles, magazines, journals, or other information related to the discussion to find variables related to Hasan al-Bana's thoughts in Islamic Education Hasan al-Banna applied teaching methods that are based on humanism , democratic and egalitarian and not doctrinal. He prioritizes qudwah hasanah, taming the heart before getting to know him more, getting to know students before giving tasks, adjusting them to the abilities of students. Give motivation and reward before punishing, and prioritize the principle of Shari'a over branches.